Sem vso noč lutal v krogu Simbolika krožnega gibanja v evropski tradicijski kulturi - Mencej, Mirjam (Studia Mythologica Slavica Supplementa, 2013)
This book ('I was wandering in circles the whole night long. The symbolism of circular movement in European traditional culture') researches the common symbolism of the circular movement in European tradition and culture through the ethnographical, historical and linguistic sources from different regions of Europe and from different historical periods. The circular movement is identifyed as the movement which is in traditional world view and understanding of the space caracteristic for the movements between this world and the other. At the same time it enables the communication between the worlds and transmition from one to the other.